PERAN GREEN TRUST MEMEDIASI PENGARUH GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE INTENTIONS - Pradnyadewi, Ni Luh Putu Martha; Warmika, I Gde Ketut (E-Jurnal Manajemen, 2019)
This study aimed to determine the effect of perceived value to the green green trust and purchase intentions green, green influence trusts to purchase green green intentions and the role of trust mediating effect of perceived value of green against green product purchase intentions Tumbler Starbucks On the Go in Denpasar. The study was conducted on the product Tumbler Starbucks On The Go in Denpasar with the number of respondents was 100 respondents. The number of respondents was determined using purposive sampling method, which is the technique of determining samples with certain considerations. Data obtained by distributing questionnaires were analyzed using path analysis (path analysis) and Sobel test. The test results of green perceived value in a positive and significant effect on trust and green green product purchase intentions Tumbler Starbucks On The Go in Denpasar. Green trust is able to mediate the influence of green perceived values ??positively and significantly on green purchase intentions. Keywords : green perceived value, green trust, green purchase intentions